Les systèmes de relations professionnelles - Bourque, Reynald (Relations industrielles / Industrial Relations, 1992)
The article reviews the book, "Les systèmes de relations professionnelles, edited by Jean-Daniel Reynaud, François Eyraud, Catherine Paradeise and Jean Saglio.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z